Milling operations in continuous flow production lines: Fräsoperation innerhalb einer kontinuierlichen Fließfertigung. Issue 1 (January 2017) - Schmidt, S.; Turan, E.; Abele, E.
Abstract : Within the Collaborative Research Center CRC 666 at the TU Darmstadt bifurcated structures in integral style are produced out of steel sheet band. In this context, the cutting technology is used to prepare the semi‐finished product for subsequent forming and machining operations as well as to even manufacturing induced shape and dimensional inaccuracies. In contrast to conventional cutting processes, the workpiece is constantly moved because of the continuous flow production. Thus, high dynamics of the machining process are required. To meet this demand, special built machine tools and the high speed cutting (HSC) technology are applied. This article shows the achieved results in sheet metal and edge milling.